Clinical management of psoriatic arthritis. Issue 10136 (2nd June 2018) - Van den Bosch, Filip; Coates, Laura
Summary: Psoriatic arthritis, or the broader term psoriatic disease, refers to an inflammatory disorder that affects multiple organs, including the skin and joints, and that also has related extra-articular manifestations and can have comorbidities. Patients with psoriatic disease have a substantial clinical burden. Early identification leading to timely diagnosis and treatment is crucial to prevent long-term structural damage and disability and the associated socioeconomic consequences. The increase in therapeutic options, such as disease-modifying anti-rheumatic drugs, both biological and targeted synthetic, has revolutionised the treatment of skin and joint disease, and has prompted clinicians to use the full clinical picture of an individual patient to make rational treatment decisions. Current research is also focused on treatment strategies, including treat to target, early remission-induction, and tapering.